THE CORRELATION OF THE HUMAN DEVELOPMENT INDEX (HDI) TOWARDS ECONOMIC GROWTH (GDP PER CAPITA) IN 10 ASEAN MEMBER COUNTRIES (Journal of Humanities and Social Studies, 2018)
Economic growth is an important factor in the economic development of a country. There is a number of factors that can increase economic growth namely human development. The level of human development in a country array in the value of the Human Development Index (HDI). The growth rate of a country appears in the value of the Gross Domestic Product (GDP) per Capita. The influence of human power resources is shown in the value of HDI which is able to influence the level of economic growth in the value of its GDP. This study will examine the effect of HDI on economic growth in 10 (ten) ASEAN member countries during the period 2010-2016, namely Indonesia, Singapore, Malaysia, Thailand, Brunei Darussalam, Philippines, Laos, Vietnam, Myanmar, and Cambodia against its economic growth in its GDP per capita. Several literature studies such Ciobanu Oana (2015), Swaha Shome et.al (2010), Mihuţ Loana Sorina (2013), show that there are a relationship and an influence of Human Development Index's value on Gross Domestic Product (GDP) per capita. The result of this research indicates that each country has a strong and significant correlation between HDI and GDP. It is concluded that the level of HDI can affect the GDP per capita. Economic growth makes it possible to reach a high level of human development, on the one hand, increasing levels of human development leading to increase opportunities for economic growth. The causal relationship between economic growth and human development becomes a mutually influential relationship. So it is clear that the human development in the country relates to an influence of economic growth which is seen in per capita income (GDP per capita) which can be an indicator of welfare in the country.